An Individual with Both MUTYH-Associated Polyposis and Lynch Syndrome Identified by Multi-Gene Hereditary Cancer Panel Testing: A Case Report - Cohen, Stephanie A.; Tan, Christopher A.; Bisson, Ryan (Frontiers in Genetics, 2016)
The utilization of next-generation sequencing technology to interrogate multiple genes simultaneously is being utilized more frequently in hereditary cancer testing. While this has benefits of reducing cost and allowing clinicians to cast a wide net in the elucidation of their patient’s cancer, panel testing has the potential to reveal unexpected information. We report on a proband with pathogenic variants resulting in two different hereditary colon cancer syndromes. A 39-year-old male with a history of colon cancer, more than 20 colon polyps and a family history of colon cancer presented for genetic counseling. Testing with a 7-gene high-risk hereditary colon cancer panel identified a homozygous pathogenic variant, c.1187G>A (p.Gly396Asp) in MUTYH, and a likely pathogenic duplication of exon 7 in MSH2. Since this test result, the proband’s mother was diagnosed with colon cancer; subsequent genetic testing confirmed she also carries the likely pathogenic duplication in the MSH2 gene. Although the cancer risk in individuals who carry multiple pathogenic variants has not been established for combined biallelic MUTYH-associated polyposis and Lynch syndrome, the identification of multiple pathogenic variants does allow for screening for cancers associated with both syndromes and has implications for cancer risk for family members. In particular, this has significant impact on those who test negative for a known familial pathogenic variant, yet could be still be at risk for cancer due to a second pathogenic variant in a family. More information is needed on the frequency of occurrence of multiple pathogenic variants, as well as the phenotypic spectrum when multiple pathogenic variants are present.